Analisis Faktor-Faktor yang Memengaruhi Regenerasi Petani Padi di Kabupaten Serang - Erlyna Wida Riptanti; Hasna Tsalits Tammy; Susi Wuri Ani (LPPM Universitas Malikussaleh - Indonesia, 2026)
The agricultural sector ranks third as the largest contributor to Indonesia’s Gross Domestic Product (GDP). Serang Regency is the second-largest rice-producing region in Banten Province. The agricultural sector’s contribution to Serang Regency’s Regional Gross Domestic Product (RGDP) was recorded at 9,47% in 2023, highlighting the sector’s strategic role in the local economy. However, the magnitude of this contribution does not align with the current state of farmer succession, which continues to face serious challenges, marked by a low proportion of young farmers compared to older farmers. This situation could threaten the sustainability of food production as well as future socioeconomic stability. Therefore, this study aims to analyze the factors influencing rice farmer succession in Serang Regency. This study employs a quantitative approach. The study location was selected using a purposive sampling method in Serang Regency, based on its status as the second-largest rice-producing area in Banten Province. The research instrument consists of a closed-ended questionnaire using a 5-point Likert scale. The sample in this study consists of rice farmers in Serang Regency, specifically in Tanara and Cikeusal sub-districts, aged 19–39 years, with a total sample size of 105 respondents. The analysis in this study employs Structural Equation Modeling – Partial Least Squares (SEM-PLS). The results of this study indicate that individual and social factors have a positive effect on farmer succession, while inhibiting factors have a negative effect on farmer succession. Meanwhile, economic factors, motivational factors, and government policies have no effect on farmer succession.